Durgābāyi Dēśmukh : jīvita caritra - Nēti Sītādēvi (Āndhra Mahiḷā Sabha Pracuraṇa ; Ḍisṭribyūṭars, Āndhrapradēś Buk Ḍisṭribyūṭars, 1977)
Biography of Durgabai Deshmukh, b. 1909, social activist from Andhra Pradesh.